Tailoring the highest occupied molecular orbital level of poly(N-vinylcarbazole) hole transport layers in organic multilayer heterojunctions - Park, Young Ran; Kim, Hyeong Jin; Im, Sungjin; Seo, Sunae; Shin, Koo; Choi, Won Kook; Hong, Young Joon (AMER INST PHYSICS, 2016)
We report the tailoring of the electronic structure of poly(N-vinylcarbazole) (PVK) using a mixture layer of polyaniline: poly(p-styrenesulfonic acid) (PANI:PSS) in organic multilayer PVK/PANI: PSS/poly(3,4-ethylenedioxythiophene):PSS heterojunctions. The overall electronic structure of the PVK overlayer was systematically down-shifted while the work function of PANI: PSS increased as a function of the PSS-to-PANI weight ratio for the ratio range from 1 to 11 in the PANI: PSS film. The down-shift in the highest occupied molecular orbital of PVK markedly reduced the hole injection barrier from PVK to quantum-dot (QD) layers in QD-light emitting diode (QD-LED) structures, resulting in superior electrical and electroluminescent characteristics for QD-LEDs. The influences of PANI: PSS thickness on the electronic structure of PVK and the performance of QD-LEDs are also discussed. (C) 2016 AIP Publishing LLC.